(NeWGENIJ oNEGIN(B: [(NrOMAN W STIHAH(B] /s - (NpU[KIN(B, (NaLEKSANDR sERGEEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1981)
(NrOMAN (B"(NeWGENIJ oNEGIN(B", (NPO SLOWAM w(B.(Ng(B. (NbELINSKOGO (B- "(N\NCIKLOPEDIQ RUSSKOJ VIZNI(B", (NESTX (B"(NPO\MA SOWREMENNOJ DEJSTWITELXNOJ VIZNI(B, (NNE TOLXKO SO WSE@ EE PO\ZIEJ(B, (NNO I SO WSE@ EE PROZO@(B, (NNESMOTRQ NA TO(B, (N^TO ONA PISANA STIHAMI(B".s
rus
Keywords: (NkLASSI^ESKAQ PROZAs; (NrOMAN W STIHAHs